A review on processing methods for agricultural waste derived adsorbents for Pb(II) ions sequestration from wastewater. Issue 17 (22nd November 2022) - Gupta, Ritu; Gehlot, Chhagan Lal; Yadav, Sunil Kumar
ABSTRACT: This review compiles a comparative study of agricultural byproducts efficacy for wastewater purification using functionalized adsorbents for Pb(II) ions. We have compiled enormous data based on selective affinity toward Pb(II) ions. The experimental factors like pH, amount of adsorbent, time of contact, temperature, and initial concentration of ions affecting the adsorption of Pb(II) ions have also been explored. Besides, the various other adsorption kinetics and models of adsorption isotherms are discussed. Future directions of research and development of adsorptive Pb(II) ions removal from industrial wastewater are proposed.